The Characteristics of Wood Vinegar from Cocoa Pod Husks as an Antifungal Agent for Natural Rubber Sheets - Chungsiriporn, Juntima; Romyen, Arisara; Pongyeela, Prukraya; Chairerk, Nirana (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Natural rubber sheets are susceptible to fungal contamination during storage, leading to quality degradation and economic losses. Traditional antifungal treatments often involve synthetic chemicals, which raise environmental and health concerns. Wood vinegar, a byproduct of biomass pyrolysis, has emerged as a potential natural antifungal agent. The aims of this study were to evaluate the physical and chemical properties as well as the antifungal activity of wood vinegar derived from cocoa pod husks, and comparing it with wood vinegar from rubberwood and bamboo. Wood vinegar was produced through pyrolysis at 400°C, and its components were qualitatively identified using gas chromatography–mass spectrometry (GC/MS). Antifungal activity was assessed at concentrations ranging from 15% to 60% using the spread plate method to evaluate fungal inhibition. The results showed that wood vinegar from cocoa pod husks exhibited medium quality in terms of odor, color, and transparency. It had a pH of 4.8, a total soluble tar content of 0.12% (wt), a specific gravity of 1.003 g/mL, and a oBrix of 1.5. The major components of cocoa pod husk wood vinegar were acetic acid (36.90%) and phenol (4.61%), with concentrations close to those found in bamboo wood vinegar. Wood vinegar from cocoa pod husks demonstrated inhibitory effects on fungal growth, significantly reducing fungal counts on rubber sheets. Higher concentrations of wood vinegar correlated with greater fungal inhibition, with a 60% concentration reducing fungal growth to 5.6 × 104 CFU/g, while the control rubber sheet had 1.1 × 10⁶ CFU/g during storage. However, at the same concentration, wood vinegar derived from rubberwood exhibited the highest antifungal efficacy, followed by bamboo, while cocoa pod husk wood vinegar showed the least effectiveness among the three.